2014
DOI: 10.1182/blood-2014-07-577619
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive issues in sickle cell disease

Abstract: As medical advances improve survival, reduce disease-related morbidity, and improve quality of life, reproductive issues will take higher priority in the sickle cell disease (SCD) community. A wide variety of topics are addressed in this chapter, including fertility, gonadal failure, erectile dysfunction, and menstrual issues in SCD. Etiologies of impaired male fertility are multifactorial and include hypogonadism, erectile dysfunction, sperm abnormalities, and complications of medical therapies. Much less is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 78 publications
2
43
0
Order By: Relevance
“…Adolescents and adults with SCD may experience a wide array of reproductive issues including delayed puberty, hypogonadism, infertility, and pregnancy complications [118][119][120][121]. In men with SCD, vaso-occlusion and recurrent testicular infarction may contribute to hypogonadism [122,123].…”
Section: Reproductive Health In Adults With Scdmentioning
confidence: 99%
“…Adolescents and adults with SCD may experience a wide array of reproductive issues including delayed puberty, hypogonadism, infertility, and pregnancy complications [118][119][120][121]. In men with SCD, vaso-occlusion and recurrent testicular infarction may contribute to hypogonadism [122,123].…”
Section: Reproductive Health In Adults With Scdmentioning
confidence: 99%
“…As serious and even mortal SRH implications exist in these disease states, [36][37][38] analogous investigation into SRH care is needed. The findings of this study may help inform other subspecialty providers of both a patient need and an avenue to improve existing comprehensive care models.…”
Section: Theme 4: Women With Cf Prefer Early Open-minded Srh Discussmentioning
confidence: 99%
“…Studies among mice have shown that increased doses of HU increase testicular germ cell apoptosis, decrease sperm count, induce testicular atrophy, increase abnormal sperm morphology, and decrease sperm motility [29]. Sickle-cell-transgenic mice have hypogonadism at baseline.…”
Section: Hydroxyurea (Hu) and Fertility In Men With Scdmentioning
confidence: 99%
“…HU is a ribonucleotide reeducates inhibitor which acts as a S-phase-specific cytotoxic agent that impairs DNA synthesis [29]. Its effects are short lived and cease to exist once the drug is removed.…”
Section: Hydroxyurea (Hu) and Fertility In Men With Scdmentioning
confidence: 99%
See 1 more Smart Citation